Low-Cost, Accurate, Effective Treatment of Hypertensive Cerebral Hemorrhage With Three-Dimensional Printing Technology - Li, Ke; Ding, Xiangqian; Wang, Qingbo; Fan, Gangxian; Guo, Wei; Li, Chenglong; Li, Meng; Li, Zefu (Frontiers in Neurology, 2021)
Background: Hypertensive intracerebral hemorrhage (HICH) is an acute, severe neurosurgical disease. Puncture drainage of the hematoma has gradually been accepted as a surgical treatment for HICH because of its minimally invasive nature. The precision of the puncture is extremely high due to particular physiological functions. The purpose was to explore the effect of a three-dimensional printed (3DP) navigation mold in the surgical treatment of HICH. Material and Methods: We used 3DP technology to assist in the puncture drainage of hematomas to construct a medical technique that is both individualized to the patient and precise. We treated 128 HICH patients using two different surgical approaches and then analyzed them retrospectively. Altogether, 61 patients were treated with minimally invasive surgery using 3DP navigation and 67 patients who underwent craniotomy to remove the hematoma through a small bone window. The clinical data for the two groups were compared postoperatively. Results: The duration of the surgery was significantly longer in the craniotomy group than in the 3DP group (3.27  1.14 h vs. 0.51  0.20 h). Postoperative complication rates were significantly lower in the 3DP group than in the craniotomy group (18.0% vs. 34.3%). Moreover, the rate of patients with a Glasgow Outcome Score score ≥4 points was not statistically significantly different in the two groups (P>0.05). Conclusion: Minimally invasive surgery assisted by 3DP navigation to treat patients with HICH is safe and effective. The 3DP technique improves the individualization and accuracy of the surgery.